Pronomes locativos em textos de dramaturgia: uma análise funcionalista - Barcellos, Rodrigo da Costa (2012)
Under the focus of the linguistic functionalism, according to Givón (2001), Bybee (2003), Furtado da Cunha, Oliveira and Martelotta (2003) and Traugott and Dasher (2005), analyzes the usage patterns of locative adverbial pronouns aí, ali, aqui, cá e lá, and its expressions bonded to the preposition de, in training daí, dalí e daqui. The definition of these five objects of investigation due to the high frequency with which they are used in relation to other adverbial class members, as proposed by Givón (2001). After exhaustive survey texts of drama in the Portuguese language - written in Brazil and Portugal - in the eighteenth, nineteenth and twentieth centuries, the objective is to make interpretive description of the functional patterns that mark the use of pronouns. This objective corresponds to the largest general hypothesis according to which, the use of these pronouns tends to postverbal position in contemporary Portuguese, especially in the prototype function (OLIVEIRA, 2007, 2009). That is, when there are more specific references, relating to physical spaces or definable, and when scope is the verbal element to adjunctive role. Regarding the analysis, based on factors related to the ordering of pronouns as referencing, namely, whether the pronoun refers to another place or circumstance; the phoricily, that is, the type of reference assumed by the locative, considering the exophoric, anaphoric or cataphoric adverbial pronoun; and what is called frame, which is related to the syntatic and semantic issues, built on the relationship between the verb, its arguments and locative pronoun. Among the survey results, one can mention: (1) tendency of locatives are located in positions adjacent to the verb, (2) the higher occurrence of pre-verbal aí, as evidence of their derivation of meaning and function, towards the connective use (Paiva, 2001), (3) In relation to cá, presents post-verbal and virtual sense, (4) in relation to the reference, the pronouns compete between concrete and virtual physical, hence the high occurrence of pronouns in the intermediate category, and aqui, remains more concrete, bounded, (5) In the nineteenth century, already appear there and here primarily virtual, (6) in relation to phoricily appear more exophorics sentences; (7) the space frame was more recurring, especially with aqui and lá. It is considered that many of the results obtained should also be the type of text worked (drama), and not specifically to centuries studied.